Hambatan dalam Penerapan Konstruksi Berkelanjutan pada Penyelenggaraan Infrastruktur - Adu, Markus Reinaldi Nikodemus; Messah, Yunita A.; Hangge, Elsy E.; Bolla, Margareth E. (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
The construction industry has an important role in economic growth, but construction activities have a significant impact on the environment, so the implementation of sustainable construction is very important. This study aims to evaluate the extent of the application of sustainable principles in infrastructure implementation in East Nusa Tenggara Province and identify the main obstacles. The data collection method used questionnaires and interviews with 33 Commitment Making Officials (PPK). The data obtained was analyzed using mean and standard deviation statistical analysis as well as content analysis to obtain the constraints. The results of the analysis show that the percentage of sustainable construction implementation in NTT is 77.32%, which is included in the predicate of "Intermediate" according to the Regulation of the Minister of PUPR No. 9 of 2021. The general planning stage recorded the highest percentage (83.12%), while the demolition stage recorded the lowest percentage (60.61%). The main obstacles found include lack of data on marginalized groups, budget constraints at various stages, and low understanding of implementers on the concept of sustainable construction. Improved coordination between parties and better resource allocation are needed to optimize sustainability practices throughout the life cycle of infrastructure projects in NTT.